Longitudinal Assessment of Acute Concussion Outcomes Through SMS Text (ConText Study). Issue 1 (January 2022) - Schoenfeld, Robert; Drendel, Amy; Ahamed, Sheikh Iqbal; Thomas, Danny
Abstract : Objective: Mild traumatic brain injury (mTBI), or concussion, is a common health problem that has seen a recent increase in US adolescents. This study uses SMS text messaging (a mobile health [mHealth] tool) to report patient symptoms. We aim to better characterize mTBI recovery and hypothesize that this mHealth tool will have high retention rates and correlate with a conventional means of assessing symptoms, the Post-Concussion Symptom Inventory (PCSI). Methods: A prospective observational cohort pilot study. Thirty-one pediatric patients with acute mTBI were recruited to characterize their injury and report their symptoms via text messaging. Patients reported symptoms once every 3 days for the first 21 days, then once a week for 6 weeks. Results: There was a strong and positive correlation between the PCSI and the mHealth tool ( r s = 0.875, P < 0.000, n = 22). Retention was 74% until symptom resolution and 42% until study completion. Patients with balance deficits had a significantly higher somatization score than those with normal balance (6.53 ± 3.25 vs 2.56 ± 2.30, t (22) = 3.211, P < 0.01). Conclusions: This pilot study demonstrates that this tool is a valid and easy-to-use method of reporting pediatric mTBI symptoms—it replicates and identifies novel findings. Our results suggest that there may be a relationship between balance and the manifestation of somatic symptoms. Retention rates were lower than predicted, indicating that text messaging may not be the ideal format in this population. Text messaging may still have other applications for short-term communication/symptom measurement.